2020
DOI: 10.1177/1759720x20959570
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of osteoarthritis knee and hip quality of life (OAKHQoL): adaptation and validation of the questionnaire in the Hungarian population

Abstract: Background: At least 17% of the population suffers from osteoarthritis (OA) in Hungary, according to the European Health Interview Survey. In Hungary, until now there was no OA-specific questionnaire available for the lower limb, in order to monitor the health-related quality of life (HRQoL). This gap gave the relevance of this research. The aim of the study was to perform the Hungarian cross-cultural adaptation and validation of the French-developed Osteoarthritis Knee and Hip Quality of Life (OAKHQoL) questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…KOA is one of the common joint diseases in the elderly and it is also the main cause of knee pain and functional limitation in the elderly [ 34 , 35 ]. TKA is a relative successful and effective method for relieving pain and functional recovery of end-stage knee osteoarthritis, which has been widely carried out worldwide [ 9 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…KOA is one of the common joint diseases in the elderly and it is also the main cause of knee pain and functional limitation in the elderly [ 34 , 35 ]. TKA is a relative successful and effective method for relieving pain and functional recovery of end-stage knee osteoarthritis, which has been widely carried out worldwide [ 9 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Fekete et al, 2020 found that 15.15% of the patients had knee OA (15 out of 99 patients) for more than ten years. This study found that women are more affected by knee OA than men (12.4% and 9.9%, respectively) (Fekete et al, 2020). Furthermore, Horváth et al, 2011 found that 111 patients (out of 672, 16.5%, 70 women and 41 men) had radiographic knee OA and 2.9% of them had severe knee OA (K-L≥3) in the south-western part of Hungary (Horváth et al, 2011).…”
Section: Prevalence Of Knee Oamentioning
confidence: 99%
“…In Hungary, it was estimated that 17% of the Hungarian population had OA based on the European Health Interview Survey 2014 (Fekete et al, 2020). In addition, Fekete et al, 2020 found that 15.15% of the patients had knee OA (15 out of 99 patients) for more than ten years. This study found that women are more affected by knee OA than men (12.4% and 9.9%, respectively) (Fekete et al, 2020).…”
Section: Prevalence Of Knee Oamentioning
confidence: 99%
See 1 more Smart Citation